The curious case of case study research. - Cleland, Jennifer; MacLeod, Anna; Ellaway, Rachel Helen (Medical Education, 2021)
The conceptualisation of 'good' medical education research as hypothesis testing to identify universal truths that are generalisable across contexts has been challenged. Joining this conversation, the field of health professions education research is complex and contextual and there are ways of examining and reporting locally based activities and innovations, which can be of general value. This position leads to a focus on case study research (CSR), inquiry bound in time and place that generates thick descriptions and close interpretations to reach explanations. CSR has grown in sophistication in recent years and can inform practice and advance the science of medical and health professions education. The authors evaluated the current state of the science of CSR in the medical education literature by identifying and reviewing 160 papers. Most articles presented as 'case studies' were not in fact CSR. Moreover, most articles failed to go beyond a 'we did this' account. The authors explore definitions of CSR, and they examine dominant CSR methodologists, Yin, Stake and Merriam, and their respective approaches to CSR. They then set out some of the basic tenets of CSR (case definition, methods of data collection and analysis) and consider the logics of CSR (its structures, purposes, assumptions and symbols). CSR challenges are considered next (such as emic and etic perspectives; ethical complexities; generalisability; quality; and reporting and reflexivity). The authors conclude that context is a mechanism, which needs to be understood, and rigorous CSR provides the structures and criticality to do so, opening up new areas of understanding and inquiry. Embracing case study research has the potential to help us mature as a discipline and develop the confidence to embrace interpretive processes and resources.